Легенда об основании Праги в латиноязычной литературе XII–XV вв. - Гидулянова , Ю.В. (Philologia Classica, 2007)
The author examines extracts from Latin Medieval and Renaissance texts concerning the legend about the foundation of Prague (from Cosmas of Prague to Aeneas Silvius Piccolomini). Cosmas Pragensis narrates in his «Chronica Boemorum» that princess Libuse foretells foundation of «great city whose glory will reach the stars» and says that the city will receive its name after the word «threshold». The later authors of Latin chronicles who deal with this legend (Přibík Pulkava, Neplach, Giovanni Marignola of XIV century) and Aeneas Silvius Piccolomini (whose «Historia Bohemica», written in 1458, belongs to humanist historiography) eliminate some details or add new ones. For example, Přibík Pulkava explains why the name of the city proved to be apt. In the end of the article the author studies the hexameters of Libuše’s prophecy.